Non-Invasive Neuromodulation in the Rehabilitation of Pisa Syndrome in Parkinson's Disease: A Randomized Controlled Trial - De Icco, Roberto; Putortì, Alessia; Allena, Marta; Avenali, Micol; Dagna, Carlotta; Martinelli, Daniele; Cristina, Silvano; Grillo, Valentina; Fresia, Mauro; Bitetto, Vito; Cosentino, Giuseppe; Valentino, Francesca; et al. (Frontiers in Neurology, 2022)
Background: Pisa Syndrome (PS) is a frequent postural complication of Parkinson’s disease (PD). PS poorly responds to anti-parkinsonian drugs and the improvement achieved with neurorehabilitation tends to fade in 6 months or less. Transcranial direct current stimulation (t-DCS) is a non-invasive neuromodulation technique that showed promising results in improving specific symptoms in different movement disorders. Objectives: To evaluate the role of bi-hemispheric t-DCS as add-on to a standardized hospital rehabilitation program in the management of PS in PD. Methods: Twenty-eight patients with PD and PS (21 male, age 72.9±5.1 years) underwent a 4-week intensive neurorehabilitation treatment and were randomized to receive t-DCS (t-DCS group, n=13), 5 daily sessions (20 minutes - 2 mA) with bi-hemispheric stimulation over the primary motor cortex (M1) or sham t-DCS stimulation (sham group, n=15) with the same duration and cadence. At baseline (T0), end of rehabilitation (T1) and 6 months later (T2) patients were evaluated with both trunk kinematic analysis and clinical scales: UPDRS-III, Functional Independence Measure (FIM) and Numerical Rating Scale (NRS) for lumbar pain. Results: When compared to sham group, t-DCS group achieved a more pronounced improvement in several variables: overall posture (p=0.014), lateral trunk inclination (p=0.013) during upright standing position, total range of motion (ROM) of the trunk (p=0.012), FIM score (p=0.048) and lumbar pain intensity (p=0.017). Conclusions: Our data supports the use of neuromodulation with t-DCS as add-on to neurorehabilitation for the treatment of patients affected by PS in PD.